Novel mechanisms, treatments, and outcome measures in childhood sleep - Colonna, Annalisa; Smith, Anna B.; Pal, Deb K.; Gringras, Paul (Frontiers in Psychology, 2015)
Sleep disorders and sleep of insufficient duration and quality are on the increase due to changes in our lifestyle, particularly in children and adolescents. Sleep disruption is also more common in children with medical conditions, compounding their difficulties. Recent studies have focused on new mechanisms that explain how learning and cognitive performance depend on a good night’s sleep. Growing alongside this latest understanding is an innovative new field of non-drug interventions that improve sleep architecture, with resulting cognitive improvements. However, we need to rigorously evaluate such potentially popular and self-administered sleep interventions with equally state-of-the-art outcome measurement tools. Animated hand-held games, that incorporate embedded sleep-dependent learning tasks, promise to offer new robust methods of measuring changes in overnight learning. Portable computing technology has the potential to offer practical, inexpensive and reliable tools to indirectly assess the quality of sleep. They may be adopted in both clinical and educational settings, providing a unique way of monitoring the effect of sleep disruption on learning, leading also to a radical rethink of how we manage chronic diseases.